2016
DOI: 10.3390/rs8070608
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Utility and Uncertainty of Multi-Satellite Precipitation Products in the Mountainous Region of South Korea

Abstract: Satellite-derived precipitation can be a potential source of forcing data for assessing water availability and managing water supply in mountainous regions of East Asia. This study investigates the hydrological utility of satellite-derived precipitation and uncertainties attributed to error propagation of satellite products in hydrological modeling. To this end, four satellite precipitation products (tropical rainfall measuring mission (TRMM) multi-satellite precipitation analysis (TMPA) version 6 (TMPAv6) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 53 publications
(84 reference statements)
2
22
1
Order By: Relevance
“…We found higher correlation coefficients with TRMM (r = 0.7, Figure 6a) and lower coefficients with Hydroe (r = 0.51, Figure 6b) than those reported by Jiang et al [19] (r = 0.66). However, our results were slightly lower than those of Kim et al [21], who identified …”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…We found higher correlation coefficients with TRMM (r = 0.7, Figure 6a) and lower coefficients with Hydroe (r = 0.51, Figure 6b) than those reported by Jiang et al [19] (r = 0.66). However, our results were slightly lower than those of Kim et al [21], who identified …”
Section: Discussioncontrasting
confidence: 56%
“…The Sapucaí watershed has an average annual rainfall of 1200 mm, while Paraíba state, which is located in the semiarid region, varies from 300 to 1000 mm. Studies conducted in the mountainous regions of South Korea [21] and China [19] showed different r values. We found higher correlation coefficients with TRMM (r = 0.7, Figure 6a) and lower coefficients with Hydroe (r = 0.51, Figure 6b) than those reported by Jiang et al [19] (r = 0.66).…”
Section: Discussionmentioning
confidence: 99%
“…GSMaP provides a series of precipitation estimates with different latencies, such as near-real-time product (GSMaP-NRT), post-real-time product with MW-IR reanalysis (GSMaP-MVK), and gauge-corrected post-real-time product (GSMaP-GAUGE). These products have been used for hydrological applications, such as flash flood simulations in the Nile River basin in Egypt [51], the Huong River basin in Vietnam [52], the Karpuz River basin in Turkey [10], and the Jhelum, Chenab, and upper Indus River basins in Pakistan [53,54]; flood inundation modeling in the Thua Thien Hue Province in Vietnam [55] and the Mundeni Aru River basin in Sri Lanka [9]; daily streamflow simulations in the Tocantins-Araguaia basin in Brazil [7], the Soyang dam basin in South Korea [56], and the Biliu basin in China [8]; annual runoff analysis in West Africa [57]; and global surface runoff mapping [58]. However, most of these studies [7][8][9][10][51][52][53][54][55][56][57] mainly adopted TRMM-era GSMaP SPPs (e.g., GSMaP versions 04 and 05) for hydrological evaluations or applications, and the hydrological assessment of GPM-era GSMaP SPPs (e.g., versions 06 and 07) was rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Since the launch of the TRMM satellite on 27 November 1997, TRMM-based satellite precipitation products have undergone a series of major revisions and widely used in hydrological applications [22][23][24][25]. After over 17 years of fruitful data gathering, the spacecraft was turned off and reentered the Earth's atmosphere on June 15, 2015.…”
Section: Introductionmentioning
confidence: 99%